Sudut ATD sebagai Penanda Diabetes Mellitus Tipe-2 (DMT2) - Syam Syamsurizal (Bioscience, 2018)
Dermatoglyphic of patterns (finger prints) could be used as genetic markers with type 2 diabetes. Analysts dermatoglyphic patterns can quantitatively through several parameters: frequency fingerprint patterns (arch, loop and whorl), the number of vines, pattern type index consists of the Dankmeijer index, Furuhata index, pattern intensity index and atd angle. Atd angle is the angle formed by connecting point triradius a, t and d on the palm area. Objective studies link dermatoglyphic characteristics (atd angle) with type 2 diabetes mellitus in Minangkabau ethnic.The research method used descriptive with 132 sample consisted of 66 patients with type-2 diabetes mellitus and 66 control. Results of research on atd angle in type 2 diabetes was 40,44± 3,34 and 40,42±3,96 in controls. The results of t-test and α = 5% p value = 0.75. It can be concluded that there was no significant difference in the average of atd angle in diabetes mellitus type 2 Minangkabau ethnic.